Real-time updating of HEC-RAS model for streamflow forecasting using an optimization algorithm - Siqueira, Vinícius Alencar; Sorribas, Mino Viana; Bravo, Juan Martin; Collischonn, Walter; Lisboa, Auder Machado Vieira; Trinidad, Giovanni Gomes Villa (Revista brasileira de recursos hídricos, 2016)
ABSTRACT Real-time updating of channel flow routing models is essential for error reduction in hydrological forecasting. Recent updating techniques found in scientific literature, although very promising, are complex and often applied in models that demand much time and expert knowledge for their development, posing challenges for using in an operational context. Since powerful and well-known computational tools are currently available, which provide easy-to-use and less time-consuming platforms for preparation of hydrodynamic models, it becomes interesting to develop updating techniques adaptable to such tools, taking full advantage of previously calibrated models as well as the experience of the users. In this work, we present a real-time updating procedure for streamflow forecasting in HEC-RAS model, using the Shuffled Complex Evolution - University of Arizona (SCE-UA) optimization algorithm. The procedure consists in a simultaneous correction of boundary conditions and model parameters through: (i) generation of a lateral inflow, based on Soil Conservation Service (SCS) dimensionless unit hydrograph and; (ii) estimation of Manning roughness in the river channel. The algorithm works in an optimization window in order to minimize an objective function, given by the weighted sum of squared errors between simulated and observed flows where differences in later intervals (start of forecast) are more penalized. As a case study, the procedure was applied in a river reach between Salto Caxias dam and Hotel Cataratas stream gauge, located in the Lower Iguazu Basin. Results showed that, with a small population of candidate solutions in the optimization algorithm, it is possible to efficiently improve the model performance for streamflow forecasting and reduce negative effects caused by lag errors in simulation. An advantage of the developed procedure is the reduction of both excessive handling of external files and manual adjustments of HEC-RAS model, which is important when operational decisions must be taken in relatively short times. RESUMO A atualização em tempo real de modelos de propagação do escoamento em rios é essencial para a redução de erros na previsão hidrológica. As técnicas de atualização recentes encontradas na literatura, apesar de promissoras, são complexas e geralmente aplicadas em modelos cujo desenvolvimento demanda tempo e conhecimento muito especializado, representando desafios para sua utilização em ambientes operacionais. Dado que atualmente existem ferramentas computacionais amplamente difundidas, que reduzem tempo e simplificam a preparação de modelos hidrodinâmicos, torna-se interessante desenvolver técnicas que sejam facilmente acopladas a estas ferramentas de modo a aproveitar um modelo já calibrado e a experiência dos usuários. Neste trabalho é apresentada uma metodologia de atualização em tempo real do modelo HEC-RAS para previsão de vazões, utilizando o algoritmo de otimização Shuffled Complex Evolution - University of Arizona (SCE-UA). O procedimento consiste na atualização simultânea de condições de contorno e parâmetros no modelo hidrodinâmico, através de: (i) geração de um aporte lateral concentrado, definido por uma adaptação do hidrograma unitário adimensional do Soil Conservation Service - SCS e; (ii) estimativa do coeficiente de Manning no trecho simulado. O algoritmo opera em uma janela de otimização com a minimização de uma função-objetivo, que considera a soma ponderada dos erros quadráticos das vazões dando maior peso aos erros nos últimos intervalos com dados observados (início da previsão). Como estudo de caso, a metodologia foi aplicada em um trecho localizado na bacia do rio Iguaçu, entre a UHE Salto Caxias e o posto fluviométrico de Hotel Cataratas. Os resultados mostraram que, com um conjunto relativamente pequeno de soluções candidatas no algoritmo de otimização, é possível melhorar, de forma eficiente, o desempenho do modelo na previsão de vazões e reduzir efeitos negativos causados por erros de fase nos hidrogramas calculados. Uma vantagem da metodologia desenvolvida é que ela permite reduzir tanto a necessidade de manipulações excessivas de arquivos como de ajustes manuais do modelo HEC-RAS, o que é importante quando decisões operacionais devem ser tomadas em tempo relativamente curto.